Acute Interstitial Nephritis due to Leptospira grippotyphosa in the Absence of Weil’s Disease - Tanja Schmidhauser; Simona Curioni; Enos Bernasconi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Anicteric leptospirosis is a self-limited flu-like disease, whereas the icteric form is a severe illness characterized by multiple organ involvement or even failure. A case involving a patient with rapidly progressing renal insufficiency requiring intermittent renal replacement therapy due to Leptospira grippotyphosa in the absence of a Weil’s disease is reported.